Bifunctional samarium activated red-emitting and thermal resistant phosphor for simultaneous field emission displays and white light-emitting diodes. Issue 4 (15th February 2022) - Khan, Wasim Ullah; Khan, Waheed Ullah; Ye, Zhiqi; Boubeche, Mebrouka; Shi, Tian; Khan, Dilfaraz; Zhang, Yueli
Abstract: A series of Sm 3+ -activated Ca3 Gd(AlO)3 (BO3 )4 red-emitting phosphors were prepared by a traditional high-temperature solid-state approach. They were characterized by XRD refinements, TEM, SEM, EDS, DRS, FTIR, Raman spectra, photoluminescence (PL) spectra, and fluorescence decay curves. The microstructure of the cation-borate phosphors and the presence of Sm 3+ dopants, and their impact at the Ca and Gd sites were studied. All the samples exhibited bright red emissions caused by intra-4f transitions of Sm 3+ ions when excited at 404 nm. The optimum dopant concentration was 4mol%, and the concentration quenching (CQ) process was driven by dipole-dipole interaction using Inokuti-Hirayama, and Dexter theories. Interestingly, the temperature-dependent PL spectra manifested that the resulting phosphor had excellent thermal stability with an activation energy of 0.234 eV. Ultimately, the investigated phosphor demonstrated excellent chemical stability. The Sm 3+ -doped CGAB:Sm 3+ phosphor can convert NUV LED chips into intense red emission with Commission Internationale de l'Eclairage (CIE) diagrams of 0.615, 0.382 and high color purity of up to 95.6%. The WLED containing CG0.96 AB:0.04Sm 3+ merged with the commercial phosphors revealed low correlated color temperature (CCT≈4197 K) and high color rendering index (CRI≈89.7). Graphical abstract: EL spectrum of the fabricated Red-LED device. Inset exemplifies the coordination diagram and image for the red phosphor. UV excitation induced bright red emissions with high color purity and outstanding thermal-quenching (TQ) resistance. Luminescent pictures of the prepared Red–LED and White-LEDs device with the input current. Highlights: UV excitation induced bright red emissions with high color purity up to 95.6%. They possessed good chemical stability in an existing environment. The CG0.96 AB:0.04Sm 3+ exhibited outstanding thermal-quenching (TQ) resistance of>90.8%. Red LED and WLED devices were fabricated by using phosphor and UV LED chips.